Isotopic evidence for the late Brasiliano (500-550 Ma) ore-forming mineralization of the Araes gold deposit, Brazil - Geraldes, M. C.; Tassinari, C. C. G.; Babinski, M.; Martinelli, C. D. [UNESP]; Iyer, S. S.; Barboza, E. S.; Pinho, F. E. C.; Onoe, A. T. (Bellwether Publ Ltd, 2008)
The Araes gold deposit, located in eastern Mato Grosso State, central Brazil, is hosted in Neoproterozoic volcanosedimentary rocks of the Paraguay belt, which formed during collision of the Amazonian craton and the Rio Apa block. Ar-40/Ar-39 geochronology and Pb and S isotopic analyses constrain the timing and sources of mineralization. Three biotite flakes from two samples of metavolcanic host rock yield Ar-40/Ar-39 plateau ages between 5941 and 531 Ma, interpreted as cooling ages following regional metamorphism. Clay minerals from a hydrothermal alteration zone yield an Ar-40/Ar-39 integrated age of 503 +/- 3 Ma. Galena grains from ore-bearing veins yield values of Pb-206/(204)pb from 17.952 to 18.383, Pb-207/Pb-204 from 15.156 to 15.811, and Pb-208/Pb-204 from 38.072 to 39.681. Pyrite grains from ore-bearing veins yield values of Pb-206/Pb-204 from 18.037 to 18.202, Pb-207/Pb-204 from 15.744 to 15.901., and Pb-208/(204)pb from 38.338 to 38.800. Pb isotope variations may be explained in terms of mixing a less radiogenic lead component (mu similar to 8.4) from mafic and ultramafic basement host-rocks (Nova Xavantina metavolcanosedimentary rocks) and a more radiogenic lead component (mu similar to 9.2) probably derived from supracrustal rocks (Cuiaba sedimentary groups). Sulfur isotope compositions are homogeneous, with delta S-34 values ranging from -1.1 parts per thousand to 0.9 parts per thousand (galena) and -0.7 parts per thousand to 0.9 parts per thousand (pyrite), suggesting a mantle-derived reservoir for the mineralizing solutions. Based on the Ar, Pb, and S isotope data, we suggest that the precious metals were remobilized from metavolcanic host rocks by hydrothermal solutions during Brasilide-Panafrican regional metamorphism. The Arabs gold deposit probably formed during a late stage of the orogeny, coeval with other mineralization events in the Paraguay Belt.